2016
DOI: 10.1007/s00468-016-1361-1
|View full text |Cite
|
Sign up to set email alerts
|

Specific leaf area of European Larch (Larix decidua Mill.)

Abstract: Key messageThe specific leaf area of European larch depends on branch height and canopy depth, indicating that both, the effect of hydraulic limitations and low water potentials in greater branch heights, and light availability affect specific leaf area.AbstractSpecific leaf area (SLA) is defined as the ratio between projected leaf area and needle dry mass. It often serves as parameter in ecosystem modelling as well as indicator for potential growth rate. We explore the SLA of European larch (Larix decidua) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…This phenomenon is consistent with the theory of low light acclimation [23,70]. LMA generally demonstrated a strong correlation with photosynthesis [31,[35][36][37] due to its close association with mesophyll conductivity to CO 2 [33,34], and LMA has also served as an indicator of the potential growth rate [75]. Figure 1 shows that LMA exhibited a positive correlation with the A max , which is consistent with previous studies [38,[76][77][78].…”
Section: Discussionsupporting
confidence: 91%
“…This phenomenon is consistent with the theory of low light acclimation [23,70]. LMA generally demonstrated a strong correlation with photosynthesis [31,[35][36][37] due to its close association with mesophyll conductivity to CO 2 [33,34], and LMA has also served as an indicator of the potential growth rate [75]. Figure 1 shows that LMA exhibited a positive correlation with the A max , which is consistent with previous studies [38,[76][77][78].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, such water stress might be associated with the development of xeromorphic features, including thick cuticles and lignified cell walls, both of which would tend to reduce SLA. Another reason is related to the expression of the plant species' ability to cope with changing light [66][67][68][69][70]. Light conditions for leaves in the lower crown are shadier and worse compared to that of the leaves in the upper crown; therefore, a larger SLA is likely an adaptation to more efficiently intercept light in low-light conditions [60,71,72].…”
Section: Specific Leaf Areamentioning
confidence: 99%
“…Light conditions for leaves in the lower crown are shadier and worse compared to that of the leaves in the upper crown; therefore, a larger SLA is likely an adaptation to more efficiently intercept light in low-light conditions [60,71,72]. Certainly, both the hydraulic limitations of greater branch height and light availability may combine to impact SLA [70]. Although these two explanations have been accepted by previous studies to a certain extent, detailed physiology studies for the MB species are worth exploring further to uncover more potential reasons.…”
Section: Specific Leaf Areamentioning
confidence: 99%
“…Furthermore, Olson et al (2014) found a universal scaling between height and anatomical functional structure (i.e., hydraulic diameter). Marshall and Monserud (2003) and Fellner et al (2016) found that specific leaf area (SLA) is tightly linked to canopy structure in many conifer species.…”
Section: Introductionmentioning
confidence: 99%